Global Production Networking and Technological Change in East Asia - Yusuf, Shahid (Washington, DC: World Bank and Oxford University Press, 2013)
This book examines the effects of the changing global geography of production for the growth prospects of East Asian economies. The authors conclude that in the face of a global environment, economies in East Asia need to adapt to the changing character of global production networks and to nurture and develop technological capabilities in order to sustain their growth prospects. This is the third volume in a series of publications from a study co-sponsored by the Government of Japan and the World Bank to examine the sources of economic growth in East Asia. The study was initiated in 1999 with the objective of identifying the most promising path to development in the light of global and regional changes.